Grappling with globalisation : challenges for economic governance - Prakash, Aseem (2001)
Examines the notion of economic globalization and how it differs from other types of economic integration. Probes how globalization impacts some of the extant national institutions of economic governance. Surveys the literature on the key challenges confronting policymakers, institutional innovations required to cope with them, and the feasibility of institutional change to grapple with globalization.